Downregulation of NOX4 Expression by Roflumilast N-Oxide Reduces Markers of Fibrosis in Lung Fibroblasts - Daniela Vecchio; Alessandra Acquaviva; Beatrice Arezzini; Hermann Tenor; Piero A. Martorana; Concetta Gardi (Hindawi Limited, 2013)
The phosphodiesterase 4 inhibitor roflumilast prevents bleomycin- (BLM-) induced lung fibrosis in animal models. However, its mechanism of action remains unknown. We investigated whether roflumilast N-oxide (RNO), the active metabolite of roflumilast, can modulate in vitro the oxidative effects of BLM on human lung fibroblasts (HLF). In addition, since BLM increases the production of F2-isoprostanes that have per se fibrogenic activity, the effect of RNO on oxidative stress and fibrogenesis induced by the F2-isoprostane 8-epi-PGF2α was investigated. HLF were preincubated either with the vehicle or with RNO and exposed to either BLM or 8-epi-PGF2α. Proliferation and collagen synthesis were assessed as [3H]-thymidine and [3H]-proline incorporation. Reactive oxygen species (ROS) and F2-isoprostanes were measured. NADPH oxidase 4 (NOX4) protein and mRNA were also evaluated. BLM increased both cell proliferation and collagen synthesis and enhanced ROS and F2-isoprostane production. These effects were significantly prevented by RNO. Also, RNO significantly reduced the increase in both NOX4 mRNA and protein, induced by BLM. Finally, 8-epi-PGF2α  per se stimulated HLF proliferation, collagen synthesis, and NOX4 expression and ROS generation, and RNO prevented these effects. Thus, the antifibrotic effect of RNO observed in vivo may be related to its ability to mitigate ROS generation via downregulation of NOX4.